English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

-3(2z-7)=-3z+21-3z

=

-6z+21=-3z+21-3z

=

21-21=-3z+6z-3z

=

0=0z

z=0

2007-01-08 09:37:35 · answer #1 · answered by Elephant rider 1 · 0 0

1) Evaluate the left side to make it look like the right. First, distribute the -3 term.

-3(2z - 7) = -6z + 21

2) Break down the z term to look like the right side of the original equation:

-3z + 21 - 3z

2007-01-08 17:36:50 · answer #2 · answered by K.G. 2 · 0 0

First multiply -3 times the items in parentheses. Then get all the z's one one side of the equal sign and all the integers on the other. Calculate each side, then solve for z.

2007-01-08 17:28:46 · answer #3 · answered by Iris 4 · 0 0

fedest.com, questions and answers